PENYELESAIAN PERMAINAN STACKELBERG LINGKAR TERBUKA DINAMIS LINEAR KUADRATIK KONTINU - , Ari Suryantoko, S.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In this thesis open loop Stackelberg game of dynamic linear quadratic continuous is discussed. Stackelberg game is a game where there is a player who acts as leader and other player as a follower. Player who allowed select his or her strategy firstly called the leader and the player who selects his or her strategy secondly called a follower. It will be derived a necessary condition for the optimal solution to find the leader and follower Stackelberg equilibrium strategy. The method that used in finding the optimal solution is the optimal solution of the control problem for continuous time is performing partial derivative of the Hamiltonian function to state variable, costate variable and control by each player. It further will be derived the Riccati equations. It will be considered the relationship between the Riccati equation with the optimal control of the leader and follower, its means if the Riccati equation solution exists, then costate variable in optimal control for each player can be expressed in form of the Riccati equation solution.